“γδT Cell-IL17A-Neutrophil” Axis Drives Immunosuppression and Confers Breast Cancer Resistance to High-Dose Anti-VEGFR2 Therapy - Zhang, Zhigang; Yang, Chenghui; Li, Lili; Zhu, Ying; Su, Ke; Zhai, Lingyun; Wang, Zhen; Huang, Jian (Frontiers in Immunology, 2021)
Angiogenesis is an essential physiological process and hallmark of cancer. Currently, antiangiogenic therapy, mostly targeting the vascular endothelial growth factor (VEGF) /VEGFR2 signaling axis, is commonly used in the clinic for solid tumors. However, antiangiogenic therapies for breast cancer patients have produced limited survival benefits since cancer cells rapidly resistant to anti-VEGFR2 therapy. We applied the low-dose and high-dose VEGFR2 mAb or VEGFR2-tyrosine kinase inhibitor (TKI) agents in multiple breast cancer mouse models and found that low-dose VEGFR2 mAb or VEGFR2-TKI achieved good effects in controlling cancer progression, while high-dose treatment was not effective. To further investigate the mechanism involved in regulating the drug resistance, we found that high-dose anti-VEGFR2 treatment elicited IL17A expression in γδ T cells via VEGFR1-PI3K-AKT pathway activation and then promoted N2-like neutrophil polarization, thus inducing CD8+ T cell exhaustion to shape an immunosuppressive microenvironment. Combining anti-VEGFR2 therapy with immunotherapy such as IL17A, PD-1 or Ly-6G mAb therapy, which targeting the immunomodulatory axis of “γδT17 cells-N2 neutrophils” in vivo, showed promising therapeutic effects in breast cancer treatment. This study illustrates the potential mechanism of antiangiogenic therapy resistance in breast cancer and provides synergy treatment for cancer.